Mycobacterium tuberculosis Mycobacterium leprae : the methodical manual on microbiology, virology and immunology for the students of 2-3 courses of the medical faculty - Yeryomina, A. K.; Kamyshny, A. M.; Kirsanova, E. V.; Sukhomlinova, I. E.; Єрьоміна, Алла Кузьмівна; Камишний, Олександр Михайлович; Кірсанова, Олена Валентинівна; Сухомлінова, Ірина Євгенівна (Zaporozhye state medical university, 2016)
The methodical manual for practical lessons on microbiology, virology, immunology for the medical students of ІІ-ІІІ year of the study are approved by the Central Methods Board of ZSMU as a methodical manual on practical lessons for students of the medical faculty. The independent practical work of students is an important part of the syllabus in the course of microbiology, virology and immunology. It helps students to study this fundamental subject. The systematic independent work enables to reach the final goal in the students’ education. It is also important while preparing the students for their future clinic work with patients. These theoretical material, questions and tests help students to get ready for examination.